Social criticism through the games of fragmentation and meaning - LOGBI , Hanène (Journal of Human Sciences, 2022)
This article aims to describe, from a concrete example, how the writing processes inherited in part from the "era of suspicion" renew, even extend the ways and means of commitment to take a lucid look precisely at "emptiness and indifference that govern" postmodern society. How, then, is literary engagement built on “strategies of form ?